Testing of software projects based on function points through a machine-learning approach - Kumar, Hemant; Saxena, Vipin (International journal of advanced networking and applications, 2025)
The software projects are coded by the software engineers either through designing function points or lines of code techniques. Both methods are equally important but due to the evolution of object-oriented technology. Function points are preferred concerning lines of code for medium and long software projects. Further, the machine learning approach is useful for testing software projects based on the Python programming language. The present paper is based on the machine learning-based testing strategy to be used for long software projects written in Python by the software industries. The computed reports are depicted in the form of tables and graphs.